Olfactory and Visual Floral Signals of Hedera helix and Heracleum sphondylium Involved in Host Finding by Nectar-Foraging Social Wasps - Lukas, Kathrin; Dötterl, Stefan; Ayasse, Manfred; Burger, Hannah (Frontiers in Ecology and Evolution, 2020)
Social vespid wasps regularly forage on flowers with a generalist pollination system. However, little is known about communication between wasps and their host plants. The aim of this study was to investigate the role of olfactory and visual floral signals of Hedera helix and Heracleum sphondylium, both frequently visited by Vespula and Dolichovespula wasps for the collection of nectar. A combination of chemical, electrophysiological and spectral analyses and behavioral experiments was used to identify attractive floral signals. We identified 37 and 41 EAD-active substances (mainly terpenoids and aromatics) in H. helix and H. sphondylium, respectively. The most abundant floral compounds were 4 oxoisophorone in H. helix and linalool in H. sphondylium, followed by (E) linalool oxide furanoid in both plants. The olfactory signals were attractive for wasps; however, a combination of olfactory and visual signals made both plants more attractive than olfactory signals alone and, in the case of H. helix, also than visual traits alone. Visual traits were not attractive by themselves. Wasps were also attracted by a synthetic solution resembling the floral scent of H. helix. Our study contributes to a better understanding of the foraging behavior of vespid wasps and describes, for the first-time, floral cues that attract vespine wasps to generalist flowers.